2017
DOI: 10.1093/jmcb/mjx010
|View full text |Cite
|
Sign up to set email alerts
|

Human apo-SRP72 and SRP68/72 complex structures reveal the molecular basis of protein translocation

Abstract: The co-translational targeting or insertion of secretory and membrane proteins into the endoplasmic reticulum (ER) is a key biological process mediated by the signal recognition particle (SRP). In eukaryotes, the SRP68–SRP72 (SRP68/72) heterodimer plays an essential role in protein translocation. However, structural information on the two largest SRP proteins, SRP68 and SRP72, is limited, especially regarding their interaction. Herein, we report the first crystal structures of human apo-SRP72 and the SRP68/72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“… 8 SRP68 functions only as a heterodimeric structure with the SRP72 protein. 9 We could speculate that null SRP68 variants would be lethal on the basis of what was recently shown in Srp72 -/- mice. 10 …”
mentioning
confidence: 85%
“… 8 SRP68 functions only as a heterodimeric structure with the SRP72 protein. 9 We could speculate that null SRP68 variants would be lethal on the basis of what was recently shown in Srp72 -/- mice. 10 …”
mentioning
confidence: 85%
“…Constructs of Arabidopsis thaliana REF6 were subcloned into either a modified pET28a vector encoding a His6-MBP fusion tag or the pGEX-4T-2 expression vector 33,46 . Both the MBP and the GST fusion tags are removed from the REF6 constructs by a tobacco etch virus (TEV) protease cleavage site.…”
Section: Cloning Protein Expression and Purification Of Ref6mentioning
confidence: 99%
“…Especially, the survival analysis of the BLCA TCGA dataset further validated SRP68 and SETD3 as potential predictive candidates for the ‘NU-like’ (low-risk) or ‘PUC-like’ (high-risk) IUP. SRP68 is a key component of SRP ribonucleoprotein complex regulating endoplasmic reticulum trafficking for protein export and tumor cell mobility ( 63 65 ). We showed that low SRP68 mRNA expression was significantly associated with favorable BLCA prognosis in the TCGA dataset.…”
Section: Discussionmentioning
confidence: 99%